Single candidates in direct election in Tangerang City, Tangerang Regency, Lebak Regency, Makassar City - Ngenget, Indiana (Technium Social Sciences Journal, 2020)
This study analyzes the "single candidate" in the simultaneous local elections in Indonesia 2018, the case of Tangerang Regency, Tangerang City, Lebak Regency (Banten Province) and Makassar City (South Sulawesi Province). The method used is qualitative with descriptive explanatory research type. Data collection techniques with in-depth interviews and library research (library research). Research findings, the problem of "single candidate" occurs from the nominating stage (nomination threshold and conditions of support for individual candidates), which causes political parties to be pragmatic because they do not have the ability to compete openly, so they choose to build coalitions to meet the conditions or vote in the nominating process. Empirically found factors that encourage the occurrence of "single candidate" in Tangerang Regency, Tangerang City, Lebak Regency are incumbent candidates who have high electability so that political parties count to be pragmatic by conducting coalitions. In the case of Makassar City a "single candidate" occurred because the competitor was disqualified. The problem of "single candidate" is an empirical phenomenon of the weakness of political regeneration by political parties from the center and the regions, as well as the high dowry requirements of the bearers of the candidates. The vote recapitulation results in three regions (Tangerang Regency, Tangerang City, Lebak Regency) were won by the dominant "single candidate", while in Makassar City the "single candidate" was defeated by an empty box.